Mathematic Model for Predicting Average Pressure of Man's Socks Based on Elastic Potential Energy of Fabrics (Journal of Fiber Bioengineering and Informatics, 2014)
In this research, a mathematic model for predicting the average pressure at the lower leg caused bysocks has been built. This research establishes a relationship between the average pressure of socks,the potential energy of fabrics and the shape of the lower leg section based on the law of conservationof energy. On the basis of the result, the mathematic model has also been built up to predict averagepressure, and the model was proved by both the data of experiments and the relation between the averagepressure, the shape of the lower leg section and the elastic potential energy of the fabrics. The resultshas shown that the average pressure caused by the socks at the lower leg is related to the circumferenceof the welt as well as the circumference of calf and elasticity of the welt. The testing result shows thatthis model can be used to predict the pressure. This model will simplify the calculation method, andprovide a theoretical foundation for the accurate prediction of the pressure at any given positions.